The diffusion window in artificial intelligence: global dynamics and prospects for Europe - Pablo-Martí, Federico; Kaszowska-Mojsa, Jagoda; Santos , Juan Luis (Papeles de Europa, 2025)
In recent years, the “diffusion window” between the launch of advanced private artificial intelligence models and public access to open alternatives has noticeably shortened. Examples such as GPT-3 and BLOOM, or more recently LLaMA-4 and GPT-4.1, illustrate this acceleration, driven by lower computational costs, the rise of open communities, and strategic business decisions. Europe leads in open models, although it remains dependent on advanced hardware. The European AI Act could promote transparency and security, allowing the region to consolidate a model of open strategic autonomy and define its digital future.